Stochastic dynamic response of a tension leg platform / Oyejobi Damilola Oyewumi - Oyejobi Damilola, Oyewumi (2017)
A systematic formulation program for the computation of stochastic dynamic response of a tension leg platform (TLP) was developed and solved for the uncoupled TLP. The effect of tendon dynamics was incorporated into a coupled TLP and was discretized using the finite element method. The platform was idealized as a rigid body and the matrices of equation of motions were formulated and solved by numerical time integration. The TLP response was characterized for regular, unidirectional and directional random waves, as well as for current and wind forces. The ocean waves were simulated using the small amplitude wave theory for regular wave and the Pierson Moskowitz wave spectrum for unidirectional and directional ocean waves. The hydrodynamic forces on the TLP were calculated by modified Morison equation while the wind-drift current on the TLP was modelled with linear profile model. The aerodynamic loadings were computed by the logarithmic wind speed profile for the mean wind speed and the Simiu- Leigh and American Petroleum Institute (API) spectra were used for fluctuating wind component in uncoupled and coupled TLP models respectively. The associated nonlinearity and response-dependent nature of the TLP made the computation of equation of motions time consuming. The results of the TLP responses were reported in time history, power spectrum and statistical values. For regular wave characterization, the results revealed that the platform amplified at the wave frequency only. In contrast with regular wave modelling, the platform amplification in all degrees of freedom occurred predominantly at the surge natural degree of freedom as well as at the wave frequency for unidirectional and directional random waves. Current and wind drag forces caused steady offset displacements in all degrees of freedoms. The motion and tendon tension responses in coupled TLP were lower in magnitude compared to the uncoupled TLP except for surge response. The behaviour of TLP in parametric studies of varying wave heights, wave periods, different sea states, loss of tendon from a group of tendon legs were analysed and reported for the purpose of decision making. This work avoided solving separate equations of motions for the platform model and the tendon leg system but simultaneously coupled it together. This was accomplished by coding the mathematical derivations in a high-level programming language and commercial finite element tool. The finite element tool was not originally designed for the solution of offshore platforms but was adapted for model discretization and the application of hydrodynamic and aerodynamic loadings on the platform. The result of this research was that offshore problem with high level complexities was solved using the knowledge of Civil Engineering.